Burden of cancer mortality and differences attributable to demographic aging and risk factors in Argentina, 1986-2011 - Sonia Alejandra Pou; Natalia Tumas; Julia Becaria Coquet; Camila Niclis; María Dolores Román; María del Pilar Díaz
Abstract: The world faces an aging population that implies a large number of people affected with chronic diseases. Argentina has reached an advanced stage of demographic transition and presents a comparatively high rate of cancer mortality within Latin America. The objectives of this study were to examine cancer mortality trends in the province of Córdoba, Argentina, between 1986 and 2011, and to analyze the differences attributable to risk variations and demographic changes. Longitudinal series of age-standardized mortality rates for overall, breast and prostate cancers were modeled by Joinpoint regression to estimate the annual percent change. The Bashir & Estève method was used to split crude mortality rate variation into three components: mortality risk, population age structure and population size. A decreasing cancer age-standardized mortality rates trend was observed (1986-2011 annual percent change: -1.4, 95%CI: -1.6, -1.2 in men; -0.8, 95%CI: -1.0, -0.6 in women), with a significant shift in 1996. There were positive crude mortality rate net changes for overall female cancer, breast and prostate cancers, which were primarily attributable to demographic changes. Inversely, overall male cancer crude mortality rate showed a 9.15% decrease, mostly due to mortality risk. Despite favorable age-standardized mortality rates trends, the influence of population aging reinforces the challenge to control cancer in populations with an increasingly aged demographic structure.